Wildlife Trafficking in Thailand: Law Enforcement Problems and Challenges - CHAIAKARAPHONG, NANRAPAT (Journal of Thai Justice System, 2020)
Even though wildlife trafficking has been an alarming environmental crime in Thailand for decades, there are only few studies on this issue. This article aims to present the ineffectiveness of law enforcement against wildlife trafficking due to the lack of knowledge and skills on law enforcement, suppression, evidence collection and inadequate legal literacy on wildlife trafficking. Furthermore, there are corruption, the lack of budget on suppression, overlapping job responsibilities among officers, indifferent attitudes towards wildlife trafficking, and powerful figures behind the wildlife trafficking organizations which allow this crime to prosper in Thailand. Apart from these, Thailand’s geographical characteristics also facilitate wildlife traffickers to transport wild animals conveniently. Most importantly, there are still high demand and supply in the wildlife markets, which forces Thailand to inevitably face with the concern. Therefore, it is necessary for all sectors in Thailand to collaboratively prevent and suppress wildlife trafficking altogether.